Enhancing mathematics teachers’ pedagogical skills by using ChatGPT - Alhazzani, Noura Saud (International Journal of Innovative Research and Scientific Studies, 2024)
The primary aim of this study was to propose a conceptual framework intended to leverage the capabilities of the Chat GPT artificial intelligence model to enhance the creative teaching proficiencies of secondary school mathematics teachers. A closed interview questionnaire designed by the researcher was administered to evaluate the proficiency levels of secondary mathematics teachers using a descriptive methodology. The study sample comprised 31 mathematics teachers. Furthermore, the researcher developed a proposed conceptual framework aimed at activating the Chat GPT model to foster creative teaching skills among secondary mathematics teachers. Analysis of the data revealed that teachers demonstrated a moderate level of proficiency in the planning dimension of creative teaching while their execution and evaluation competencies were comparatively less advanced. Moreover, the study confirmed the appropriateness of the proposed conceptual framework for augmenting the creative teaching aptitudes of secondary mathematics teachers emphasizing its relevance, significance and practical utility. According to teachers’ perspectives, this framework is appropriate in light of its relevance, importance and applicability. In a nutshell, this research contributes to the discourse on innovative pedagogical strategies by proposing a viable framework for the integration of artificial intelligence technologies into mathematics education. By doing so, it seeks to nurture creativity and efficacy among teachers within the secondary school potentially enhancing the quality of mathematics instruction and student learning outcomes. These findings underscore the importance of integrating regenerative AI ChatGPT into classrooms emphasizing its role in enhancing creative teaching skills and its practical applicability in educational contexts.